Fairy tales or fairy fakes? - Kopházi-Molnár, Erzsébet (Gyermeknevelés Tudományos Folyóirat, 2022)
When adults (or children) want to find really good fairy tale books, doing so is not as simple as it seems. Although bookstores are full of children’s books, only some are worth reading. As a result, potential readers are often helpless since they cannot decide which book to choose or what qualities a good fairy tale should contain. Many rewritten versions of tales show some similarities based on the ways they have been adapted. Naturally, the modern versions are not of the same quality and range from quite good versions to absolutely bad ones. This paper will analyse how one particular type of rewritten tale is constructed through the well-know story of Cinderella. In this paper, the tales that have been created on the basis of an original are viewed as ‘redundant’, because they seem to be a kind of extension of the tale, one containing subsequent stories added to the basis. These books are sold as tales, although we will see that they do not meet the requirements of tales at all.